Von Willebrand’s disease – is a new classification system required? (Hematology Meeting Reports, 2009)
The first attempts to break down von Willebrand’s disease (VWD) into subclasses date back to the mid 1980s, predominantly based on knowledge achieved through the disseminated use of the new multimeric methods that gave way to various subclass phenotypes of VWD. In 1993-4, the VWF Subcommittee of ISTH endorsed and published a revised and simplified classification system attempting to focus more on pathophysiology and clinical characteristics in VWD, rather than merely protein phenotypic subsets. During the last 4-6 months discussions have taken place amongst members of a working group hosted by the Scientific and Standardization von Willebrand subcommittee in order to evaluate whether there is a need for revision of the present classification guideline. A major aspect in this work is the clinical approach. It is well known that the availability of laboratory tools for use in diagnosis of VWD varies considerably from center to center and therefore a new recommendation are required presenting with common diagnostic denominators for use in the VWD diagnosis. Further, concerns have been raised around the use of a VWD diagnosis in those patients who present with milder changes in level or function of plasma VWF. Highlights from the e-mail based working group discussions will be presented for further debate in the scenario of the present Nordic symposium on von Willebrand’s disease.